Molecularly-tunable nanoelectrode arrays created by harnessing intermolecular interactions. Issue 17 (10th March 2021) - Cheng, Han-Wen; Wang, Shan; Porter, Marc D.; Zhong, Chuan-Jian
Abstract : Intermolecular interactions in monolayer assembly are harnessed for creating molecularly-tunable nanoelectrode arrays or ensembles. Abstract : Intermolecular interactions play a critical role in the binding strength of molecular assemblies on surfaces. The ability to harness them enables molecularly-tunable interfacial structures and properties. Herein we report the tuning of the intermolecular interactions in monolayer assemblies derived from organothiols of different structures for the creation of nanoelectrode arrays or ensembles with effective mass transport by a molecular-level perforation strategy. The homo- and hetero-intermolecular interactions can be fully controlled, which is demonstrated not only by thermodynamic analysis of the fractional coverage but also by surface infrared reflection absorption and X-ray photoelectron spectroscopic characterizations. This understanding enables controllable electrochemical perforation for the creation of ensembles or arrays of channels across the monolayer thickness with molecular and nanoscale dimensions. Redox reactions on the nanoelectrode array display molecular tunability with a radial diffusion characteristic in good agreement with theoretical simulation results. These findings have implications for designing membrane-type ion-gating, electrochemical sensing, and electrochemical energy storage devices with molecular level tunability.